Development of rational overlay design procedures for flexible pavements - Crovetti, James A. (Wisconsin Highway Research Program, 2005)
This report presents the findings of a research study conducted to develop procedures for the design of structural Hot Mix Asphalt (HMA) overlays over existing flexible pavements in Wisconsin. The recommended procedures are presented in a hierarchal approach to allow the user the flexibility of estimating the effective structural number of an in-place HMA pavement based on visual and/or nondestructive deflection testing data and to develop overlay thickness requirements based on the structural deficiency approach. Techniques for estimating the effective structural number of an existing pavement based on surface deflection are presented. The equations presented in the 1993 American Association of State Highway and Transportation Officials (AASHTO) Design Guide were modified to enhance their applicability. Alternate deflection-based techniques were also developed to allow for the estimation of effective structural number without pavement thickness information. The overlay design procedures were developed to maintain consistency with the current Wisconsin Department of Transportation (WisDOT) practice of new flexible pavement design based on the 1972 AASHTO design equation.
72 p.
Keywords: Wisconsin; Thickness; Structural number (Pavements); Nondestructive tests; Hot mix paving mixtures; Flexible pavements; Equations; Design methods; Deflection; Bituminous overlays